Hubungan Perilaku Kebersihan Perorangan dan Lingkungan Serta Status Gizi dengan Kejadian Infeksi pada Anak Usia Sekolah di Sekolah Dasar Kota Jambi - Gusti Lestari Handayani; Abbasiah Abbasiah (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The spread of epidemiologically-based school-based disease among school children in Indonesia is still high. Cases of infection such as dengue hemorrhagic fever, diarrhea, intestinal worms, acute respiratory infections, and reactions to food due to poor sanitation and food safety. The risk of health problems in children due to environmental pollution from various processes of development activities is increasing. In addition to the environment, the problem that must be considered is to shape healthy behaviors in school children. Malnutrition can inhibit the immune response and increase the risk of infectious diseases. Infectious diseases with a person's nutritional status can be described as a reciprocal relationship. Objective of the research to find out the correlation between individual hygiene behavior and environmental hygiene and nutritional status with the incidence of infection in school age children in Jambi elementary school. Research design was cross sectional design. Data collection is done by using questionnaires. The research was conducted in 3 (three) primary schools namely SDN 40, SDN 151, SDN 131 Kota Jambi. The sample in this research is 138. Data analysis using cross chi-square statistical test. The result of statistical test showed that there was a significant correlation between individual hygiene behavior with the incidence of infectious diseases with P value 0.036, and the behavior of environmental hygiene and incidence of infectious diseases with P value 0,013 OR 3,361. While the relationship of nutritional status and incidence of infectious diseases found that there is no significant relationship with P value 0.469. It is expected that the school can improve personal and environmental hygiene efforts through cooperation with health and education providers in the form of counseling programs and personal hygiene and environmental training.